2017
DOI: 10.1016/j.semcdb.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Peromyscus transcriptomics: Understanding adaptation and gene expression plasticity within and between species of deer mice

Abstract: Deer mice in the genus Peromyscus occupy nearly every terrestrial habitat in North America, and have a long history as subjects of behavioral, ecological, evolutionary, and physiological study. Recent advances in transcriptomics, the study of the complete set of RNA transcripts produced by certain cell types or under certain conditions, have contributed to the development of Peromyscus as a model system. We review the recent use of transcriptomics to investigate how natural selection and gene expression plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…There is also evidence that Peromyscus spp. readily adapt to environmental change (Storz et al 2007, 2009, 2010; Mullen & Hoekstra 2008; Linnen et al 2009; Weber et al 2013; Natarajan et al 2013; Munshi-South & Richardson 2017), making them good subjects for the study of local adaptation. White-footed mice are one of the few native mammals that thrive in extremely small, fragmented urban forests in North America (Pergams & Lacy 2008; Rogic et al 2013; Munshi-South & Nagy 2014), and tend to be found at higher densities in urban vs. rural patches due to a thick understory providing abundant food resources and exclusion of major predators and competitors (Rytwinski & Fahrig 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that Peromyscus spp. readily adapt to environmental change (Storz et al 2007, 2009, 2010; Mullen & Hoekstra 2008; Linnen et al 2009; Weber et al 2013; Natarajan et al 2013; Munshi-South & Richardson 2017), making them good subjects for the study of local adaptation. White-footed mice are one of the few native mammals that thrive in extremely small, fragmented urban forests in North America (Pergams & Lacy 2008; Rogic et al 2013; Munshi-South & Nagy 2014), and tend to be found at higher densities in urban vs. rural patches due to a thick understory providing abundant food resources and exclusion of major predators and competitors (Rytwinski & Fahrig 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They live in a diverse array of habitats that exposes them to a variety of selective pressures, and thus, multiple Peromyscus spp. have become model systems for studies examining ecology, evolution and physiology in natural populations (Munshi-South & Richardson, 2017). There is also evidence that Peromyscus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity adaptations in three-spine sticklebacks: [1,2]; high-altitude adaptations for hemoglobin in deer mice and humans: [3,4]; and Peromyscus adaptations for multiple environments: [5][6][7]). The match between organism and environment must be studied in the context of both components of fitness: survival and reproductive success, because both aspects of selection are critical to long term persistence in a given environment.…”
Section: Introductionmentioning
confidence: 99%
“…MacManes [35] also recently conducted differential gene expression analyses on cactus mouse kidneys subjected to acute dehydration to explore transcriptomic renal responses. However, the transcriptomic resources available for this species extend considerably beyond renal tissue; transcripts from cactus mouse (as well as numerous other Peromyscus species) have been heavily utilized to pursue questions related to multiple aspects of evolutionary biology (reviewed in [5,7]). Current investigations into cactus mouse desert-adaptive renal physiology include transcriptomic analyses [35]; however, we extended this genetic approach by shifting the focus from adaptions for survival to include physiological adaptations for reproductive success [33].…”
Section: Introductionmentioning
confidence: 99%
“…comparative studies of gene expression in closely related species exhibiting different patterns of mating behavior promise to yield important insights into the transcriptomic causes and consequences of differences in mammalian behavior (Bengston et al, 2018;Munshi-South & Richardson, 2017).…”
mentioning
confidence: 99%